2017
DOI: 10.1002/chem.201704251
|View full text |Cite
|
Sign up to set email alerts
|

A “Signal On” Photoelectrochemical Biosensor Based on Bismuth@N,O‐Codoped‐Carbon Core‐Shell Nanohybrids for Ultrasensitive Detection of Telomerase in HeLa Cells

Abstract: Core-shell nanohybrids (NHs) with good semiconducting properties are vital to promote optoelectronic, photocatalytic, biosensing and bioelectronics technologies. Although great process has been achieved, synthesis of NHs composed of semiconductor core and heteroatom-doped nanocarbon shell remains a challenge, and their applications in photoelectronchemical (PEC) biosensors have not been explored. Herein, the synthesis and properties of a Bi nanocrystal and N,O-codoped carbon (NOC) core-shell NHs (Bi@NOC) is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Zhou et al mixed and stirred a GO suspension, 30% hydrogen peroxide (H 2 O 2 ), and ferric chloride (FeCl 3 ·6H 2 O) solution and irradiated it with a mercury lamp to prepare fluorescent CDs with good crystallinity. [ 41 ] In recent years, an improved nitric acid oxidization method for preparing CDs from industrial W45 carbon black (WCB) was reported, [ 42 ] and CDs with dual‐tunable luminescence characteristics were obtained, which were closely related to the effects of the oxygen doping process ( Figure 4 D). This method offers the advantages of low cost and small particle size of the CDs, and the product may have different colors of light, but the synthesis process is complicated, which is not beneficial for product collection.…”
Section: Fabrication Of Cdsmentioning
confidence: 99%
“…Zhou et al mixed and stirred a GO suspension, 30% hydrogen peroxide (H 2 O 2 ), and ferric chloride (FeCl 3 ·6H 2 O) solution and irradiated it with a mercury lamp to prepare fluorescent CDs with good crystallinity. [ 41 ] In recent years, an improved nitric acid oxidization method for preparing CDs from industrial W45 carbon black (WCB) was reported, [ 42 ] and CDs with dual‐tunable luminescence characteristics were obtained, which were closely related to the effects of the oxygen doping process ( Figure 4 D). This method offers the advantages of low cost and small particle size of the CDs, and the product may have different colors of light, but the synthesis process is complicated, which is not beneficial for product collection.…”
Section: Fabrication Of Cdsmentioning
confidence: 99%
“…[49] In addition, Li et al have successfully prepared another core-shell structured MnS@Bi 2 S 3 NPs for MR,C T, and PA trimodal tumor imaging. [51] Besides in vivoi maging abilities for cancerd iagnosis, some Bi-based NMs have been used for photoelectrochemical detection of tumor marker.F or instance, Liu et al have designed Bi@carbon core-shell nanohybrids to detect telomerase in HeLa cells due to their excellent photoelectrochemical activity originated from their semiconducting feature with the band gap of 1.14 eV; [56] BiOI@graphiticc arbon nitride nanocomposites have also been designed to detect carcinoembryonic antigen because of their staggered energy bands, which can inhibit photoinduced electrons and holes recombination, thus improvingt he photoelectrochemical activity and further displaying ultrahigh sensitivity of carcinoembryonic antigen. [57]…”
Section: Multimodali Magingmentioning
confidence: 99%
“…For instance, Liu et al. have designed Bi@carbon core–shell nanohybrids to detect telomerase in HeLa cells due to their excellent photoelectrochemical activity originated from their semiconducting feature with the band gap of 1.14 eV; BiOI@graphitic carbon nitride nanocomposites have also been designed to detect carcinoembryonic antigen because of their staggered energy bands, which can inhibit photoinduced electrons and holes recombination, thus improving the photoelectrochemical activity and further displaying ultrahigh sensitivity of carcinoembryonic antigen …”
Section: Bi‐based Nms Used For Cancer Diagnosismentioning
confidence: 99%
“…[1] Among these biomolecules, nucleic acids are commonly investigated. Numerous techniques have been derived, such as enzymatic amplification, [3] nanotechnology [4,5] and polymeric materials. However,t he content of nucleic acids related to lung canceri sfrequently at an extremely low leveli n the early stages of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been invested to improve the detection sensitivity of nucleic acids in the past decade. Numerous techniques have been derived, such as enzymatic amplification, nanotechnology and polymeric materials . Among them, point‐of‐care testing of nucleic acids can be realized by directly introducing polymeric materials to nucleic acids.…”
Section: Introductionmentioning
confidence: 99%